Exploring Gender, Computational Making and E-Textiles using the BBC micro:bit - Rode, Jennifer Ann; Barkhuus, Louise; Ioannou, Andri (My University, 2024)
We present a qualitative study of a Cypriot summer school where we used the BBC micro:bit to examine gender inclusivity in etextiles. We employed the Computational Making framework to analyze ethnographic data teaching 24 middle school students, aged 10-15. The study contrasts the challenges faced by students using the micro:bit with those from our team's previous similar e-textile studies using the LilyPad Arduino. We pinpoint the BBC micro:bit's limitations from an inclusive design perspective, underscoring the absence of gender-sensitive considerations in its hardware design. The paper presents a critique how upwards of £75 Million were spent deploying the micro:bit without proper user studies of gender equity and e-textiles. We propose design recommendations for future BBC micro:bit versions, advocating for integrating a gendersensitive participatory design approach to enhance the usability and engagement of computational and creative making with e-textiles for children of all genders.
Keywords: BBC micro:bit; Children; Computational Making; Computational Thinking; E-textiles